Topically applied pH-responsive nanogels for alkyl radical-based therapy against psoriasiform hyperplasia - G.R. Nirmal; Chia-Chih Liao; Zih-Chan Lin; Abdullah Alshetaili; Erica Hwang; Shih-Chun Yang; Jia-You Fang (Taylor & Francis Group, 2023)
AbstractPhototherapy is a conventional antipsoriatic approach based on oxygen-relevant generation of oxidative stress to inhibit keratinocyte hyperproliferation. However, this therapy can be restricted due to local hypoxia in psoriatic lesions. The generation of alkyl radicals is oxygen-independent and suppresses hyperproliferation. Herein, we established alkyl radical-based therapy to treat psoriatic hyperplasia. Because alkyl radicals are short-lived compounds, we loaded 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride (AIPH) as a precursor of alkyl radicals into the chitosan nanogels to improve stability. The present study presented a topically applied nanogel that led to a pH-responsive network sensitive to skin pH. This pH responsiveness of the nanogels allowed fast alkyl radical release in the target site. The physicochemical properties of the prepared nanogels were determined through size, zeta potential, scanning electron microscopy, and absorption spectroscopy. The antipsoriatic activity was examined with keratinocyte- and animal-based studies. The nanogels displayed a smooth and spherical morphology with a hydrodynamic diameter of 215 nm. This size was largely increased as the environmental pH increased to 6. The nanogels heated at 44 °C produced alkyl radicals to induce keratinocyte death through the necrosis pathway. Bioimaging demonstrated that topically applied nanogels could deliver alkyl radicals into the epidermis. This targeting was accompanied by the accumulation of free radicals in the epidermis according to the 2',7'-dichlorodihydrofluorescein diacetate assay. The imiquimod-stimulated psoriasiform animal model indicated a remarkable reduction in erythema, scaling, and overexpressed cytokines upon topical treatment of the nanogels. The transepidermal water loss of the psoriasiform skin was inhibited from 51.7 to 27.0 g/m2/h, suggesting barrier function recovery by the nanocarriers. The nanogels lowered hyperplasia by decreasing the epidermal thickness from 212 to 89 μm. The incorporation of 8-hydroxypyrene-1,3,6-trisulfonic acid (HPTS) as a pH-sensitive fluorescence dye in the nanogels could be used to diagnose the severity of the psoriasiform plaque due to the stronger fluorescence of HPTS in skin with lower pH (psoriasiform skin pH = 4.4) than in healthy skin (pH = 4.9). It was possible to deliver the prepared nanogels into the epidermis to restrain hyperplasia without causing cutaneous irritation.